Déols, places Carnot et La Fayette : mutation fonctionnelle d’un espace, entre cimetière paroissial et place, du Xe au XIXe siècle (Indre) - Gwenaël Roy; Françoise Yvernault (Revue Archéologique du Centre de la France)
Archaeological observations carried out in 2010 before the redevelopment of the Carnot and La Fayette’s squares in Déols (Indre) have allowed the exploration of nearly 13,000 m² in the city center. The information collected concerns the mutations of a space around the Saint-Étienne church whose function alternates between churchyard and place during the medieval and modern periods. Masonry was also uncovered, among which a massif could be correspond to the Sainte-Marie’s chapel, which has now disappeared. The comparison between the data with those acquired in the second half of the twentieth century refines the understanding of the evolution of the spatial organization of this central space of Déols between the 10th and 19th centuries.